The archaeological activities of James Douglas in Sussex between 1809 and 1819 - Lyne, M. A. B. (Archaeological lives., 2017)
James Douglas (1753-1819) was a polymath, well ahead of his time in both the fields of archaeology and earth-sciences. This text recounts his archaeological and other activities in Sussex during the first two decades of the 19th century.